Investigating the performance-related properties of crumb rubber modified bitumen using rheology-based tests. Issue 3 (23rd February 2022) - Rochlani, Mrinali; Leischner, Sabine; Wareham, David; Caro, Silvia; Falla, Gustavo Canon; Wellner, Frohmut
ABSTRACT: In recent years, crumb rubber (CR) has become an attractive option to modify bitumen. In this research, a set of Dynamic Shear Rheometer (DSR) tests were used were used to gauge the effect of two types of CR on different rheological and mechanical properties of CR bitumen (CRB). To achieve this goal, temperature and frequency sweep tests were conducted on three CRB and one penetration 50/70 reference bitumen, and Single Stress Creep Recovery (SSCR) tests were used to quantify the susceptibility of the bitumen to permanent deformation. Moreover, a new specialised cryogenic test and a recently developed fatigue test conducted on prismatic and cylindrical column bitumen samples, respectively, were implemented using the rheometer, and used to assess the low-temperature cracking and fatigue behaviour of the materials. The results indicate that the improvement in all performance-related properties by adding CR into bitumen can be evaluated by using one single device. A performance diagram developed by the authors was used to visualise and compare the effects of adding CR to the bitumen in regards to their rheological, low temperature, permanent deformation and fatigue performance properties.